Concepts, compass and computation: Models for directional part-whole relationships - Singh, G.; De By, R.; Ivanova, Ivana (2012)
We present a conceptual framework and computational mechanism to allow the interpretation of text phrases such as "in southeastern Bahia," and "in central Goiás" as spatial features in GIS context. The framework recognises different notions of centre, central sector and outer sector, from which a variety of interpretation models is derived. We subsequently evaluate these models for the performance characteristics of precision and recall, against a digitised, natural history gazetteer for Brazil, and draw conclusions on the cognition of, and computation with directional part-whole relationships. © 2012 Springer-Verlag.